1996
DOI: 10.1111/j.1600-0609.1996.tb01390.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of serum levels of soluble CD23 and tumor necrosis factor alpha in low‐grade non‐Hodgkin's lymphoma

Abstract: In the last few years the research for new biological features in low‐grade non‐Hodgkin's lymphoma has provided important results. Several biological parameters are under evaluation and, in particular, cytokines and soluble receptors levels are showing their importance as prognostic parameters. In the present study, serum levels of tumor necrosis factor alpha (TNF‐α) and soluble CD23 (sCD23) were measured at the time of diagnosis and after induction polychemotherapy in 40 patients with newly diagnosed low‐grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In patients with untreated CLL and DLBCL, increasing serum IL-10 levels were correlated with inferior survival [40]. Also, high levels of TNF in pre-treatment samples of NHL patients were correlated with poor outcome [36], and there was a significant decrease in serum TNF reported in low-grade NHL patients who achieved a complete response to standard chemotherapy [41]. In the current phase 1 study with a limited number of patients and samples, we found no correlation between levels of TNF or IL-10 and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with untreated CLL and DLBCL, increasing serum IL-10 levels were correlated with inferior survival [40]. Also, high levels of TNF in pre-treatment samples of NHL patients were correlated with poor outcome [36], and there was a significant decrease in serum TNF reported in low-grade NHL patients who achieved a complete response to standard chemotherapy [41]. In the current phase 1 study with a limited number of patients and samples, we found no correlation between levels of TNF or IL-10 and response to treatment.…”
Section: Discussionmentioning
confidence: 99%